Carbon dioxide capture by metal organic frameworks - Saha, Subhadeep; Chandra, Suman; Garai, Bikash; Banerjee, Rahul (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
The design and synthesis of functionalized metal organic framework materials (MOFs) for reversible physisorption of CO2 is discussed. This strategy of CO2 adsorption in MOFs requires less energy for regeneration than materials relying on chemisorption. As a result the MOFs have received considerable attention as sorbent materials for strategic gases such as CO2 and H,. In this review, we have discussed different MOFs and hybrid materials containing MOFs which can adsorb CO2 at room temperature. In order to achieve high adsorption capacity, fast CO2 adsorption-desorption and low energy requirement for regeneration are necessary. Several avenues for increasing the CO2 adsorption capacity of such materials, for instance, introduction of open metal sites and the use of ligand molecules with specific functionalities (like -OH or -NH2) have been described. It has been observed that CO2 loading capacity of MOFs increases with functionalization. Herein, we have discussed how N-containing and fluorinated MOFs are designed to achieve higher CO2 loading than their non-functionalized counterparts. Nanocarbons (e.g. carbon nanotubes, carbon nanofibres, etc.) are porous materials and a blend of these porous materials with porous MOFs or porous carbon derived from MOFs may act as a better adsorbate than even the pure materials. Enhancement of CO2 loading by nanocarbon-MOF hybrid material is also discussed.
Keywords: Carbon dioxide adsorbents; Carbon dioxide capture; hybrid materials; Metal organic frameworks; Nanocarbons; Porous nanocarbons

Carbon dioxide capture using amine functionalized silica gel - Sakpal, Tushar; Kumar, Asheesh; Kamble, Sanjay; Kumar, Rajnish (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Commercially available silica gel is chemically modified for carbon dioxide capture. Calcinated silica gel of certain particle size functionalized with amine using two different methods, wet impregnation and grafting via silane chemistry has been employed as a porous media. The prepared material is characterized by Fourier transform infrared, scanning electron microscopy, energy dispersive analysis of X-rays, thermogravimetry and N-2 physisorption techniques. Gas uptake measurements have been carried out to ascertain the CO2 capture capacity of the amine functionalized material. The experiments have been carried out at moderate pressure and temperature range to ascertain its potential for easy scale up.
Keywords: Amine functionalized silica gel; Carbon dioxide capture; grafting; Poly(ethyleneimine); Silane chemistry; Wet impregnation

HBGS (hydrate based gas separation) process for carbon dioxide capture employing an unstirred reactor with cyclopentane - Ho, Leong Chuan; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
The effect of CP (cyclopentane) as a promoter/additive, in the HBGS (hydrate based gas separation) process for pre-combustion gas mixture was investigated by employing an unstirred reactor configuration. Gas uptake measurements were performed at two different temperatures (275.7 K and 285.7 K) and at an experimental pressure of 6.0 MPa to determine the kinetics of hydrate formation. Experiments were conducted with three different volumes (7.5, 15 and 22 ml) of CP and based on induction time and the rate of hydrate growth, 15 ml of CP was determined to be the optimal volume for carbon dioxide capture at 6.0 MPa and 275.7 K. In addition, the effect of a kinetic promoter, SDS (sodium dodecyl sulfate), was investigated. Surprisingly, no improvement in kinetic performance was observed at 6.0 MPa and 275.7 K in the presence of SDS and CP. From the study, it was found that at the optimal 15 ml CP (CP layer thickness of 1.8 mm), the average composition of carbon dioxide in the hydrate phase was 90.36 mol% with a separation factor of 17.82. Furthermore, the unstirred reactor also yielded better kinetic performance over the stirred tank reactor with the unstirred reactor having a 2.28 times higher average gas uptake. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Cyclopentane; Gas hydrates; Gas separation; Pre-combustion; Unstirred reactor

Hydrate phase equilibrium of ternary gas mixtures containing carbon dioxide, hydrogen and propane - Babu, Ponnivalavan; Yang, Ting; Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Journal of Chemical Thermodynamics, 2013)
Hydrate phase equilibrium of the ternary guest mixtures containing carbon dioxide, hydrogen and propane at two different compositions were determined. Addition of mole composition of 2.5% propane to the fuel gas (CO2 (40%)/H-2 (60%)) mixture reduces the hydrate formation conditions by 66% at the temperature of 278.4 K. A Clausius-Clapeyron plot for the experimental results was plotted and from the slope, the enthalpy of hydrate dissociation was calculated. The enthalpy of dissociation of the mixed hydrate formed from a ternary gas mixture containing mole composition 38.1% CO2, 59.4% H-2 and 2.5% C3H8 was found to be 110 kJ.mol(-1) and hence it was concluded that the mixed hydrate formed structure II (sII) hydrates. Whereas for the ternary gas mixture containing mole composition 80.0% CO2, 18.8% H-2, and 1.2% C3H8, the enthalpy of dissociation of the mixed hydrate was found to be 78 kJ.mol(-1) and hence we believe the mixed hydrate formed structure I (sI) hydrate. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Phase equilibrium; Pre-combustion; Thermodynamics

Influence of contact medium and surfactants on carbon dioxide clathrate hydrate kinetics - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Fuel, 2013)
Carbon dioxide (CO2) hydrate formation kinetic was investigated in a fixed bed crystallizer at constant pressure (3.55 MPa) and temperature (274 K). Porous media of three different silica gels were used, with a mesh size of 60-120, 100-200 and 230-400 having different surface area. The observed trends indicate that silica gel with larger surface area leads to higher gas consumption as well as reduces the induction time. The effect of pore diameter and particle size distribution has already been reported in a previous study [1]. In this study the effect of additives on hydrate formation kinetics were also investigated. The additives studied were nonionic surfactant Tween-80 (T-80), cationic dodecyltrimethylammonium chloride (DTACl) and anionic Sodium Dodecyl Sulphate (SDS). Out of the three surfactants used in this study, SDS was found to be most effective in enhancing the rate of hydrate formation as well as reducing the induction time. The current result shows significant improvement in water to hydrate conversion in silica gel media compared to quiescent water or surfactant-water system under similar conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrate; kinetics; Silica gel; Surfactants

Medium pressure hydrate based gas separation (HBGS) process for pre-combustion capture of carbon dioxide employing a novel fixed bed reactor - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (International Journal of Greenhouse Gas Control, 2013)
This work presents an effective medium pressure hydrate based gas separation (HBGS) process for pre-combustion carbon dioxide capture in a novel fixed bed column. 2.5 mol% propane was added to the fuel gas mixture as an additive to decrease the operating pressure of the HBGS process. Hydrate formation kinetics was investigated at three different pressures (4.5, 5.5 and 6.0 MPa respectively) and at 274.15 K. The performance of silica sand and silica gel as a medium was evaluated. In silica sand bed, multiple nucleation events were observed. In silica gel bed, the gas uptake and water conversion to hydrates was significantly low at any given driving force than that obtained in silica sand bed. Experiments at different water saturation levels (50, 75 and 100%) in silica sand bed were investigated at 6.0 MPa and 274.15 K. It was found that at 50% water saturation, gas consumed for hydrate formation and water conversion to hydrates was almost three times that at 100% saturation. Water to hydrate conversions of up to 64.3% was achieved after 4 h of hydrate formation for the 50% water saturated silica sand bed. Our study presents an opportunity to scale up the HBGS process for CO2 capture with enhanced kinetics by employing a fixed bed reactor configuration. Decomposition experiments at a driving force of Delta T of 10 K and 23K were carried out to recover the gas consumed for hydrate formation and it was found that Delta T of 23 K was sufficient to recover the hydrated gas. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Pre-combustion; Separation

Pre-combustion capture of carbon dioxide in a fixed bed reactor using the clathrate hydrate process - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
Hydrate based gas separation (HBGS) process with silica sand and silica gel as contact medium was employed to capture CO2 from fuel gas mixture. Gas uptake measurement at three different pressures (7.5, 8.5 and 9.0 MPa) and 274.15 K were conducted for hydrate formation kinetics and overall conversion of water to hydrate, rate of hydrate formation were determined. Water conversion of up to 36% was achieved with silica sand bed compared to 13% conversion in the silica gel bed. Effect of driving force on the rate of hydrate formation and gas consumption was significant in silica sand bed whereas it was found to be insignificant in silica gel bed. Hydrate dissociation experiments by thermal stimulation (at constant pressure) alone and a combination of depressurization and thermal stimulation were carried out for complete recovery of the hydrated gas. A driving force of 23 K was found to be sufficient to recover all the hydrated gas within 1 h. This study indicates that silica sand can be an effective porous media for separation of CO2 from fuel gas when compared to silica gel. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrates; Gas separation; Global warming; Pre-combustion

Enhanced kinetics for the clathrate process in a fixed bed reactor in the presence of liquid promoters for pre-combustion carbon dioxide capture - Babu, Ponnivalavan; Ho, Chie Yin; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
In this work, we present enhanced kinetics of hydrate formation for the clathrate process in the presence of two liquid promoters namely THF (tetrahydrofuran) and TBAB (tetra-n-butyl ammonium bromide) in a FBR (fixed bed reactor) for pre-combustion capture of CO2. Silica sand was used as a medium to capture CO2 from CO2/H-2 gas mixture by hydrate crystallisation. Experiments were performed at different temperatures (274.2 K and 279.2 K) and 6.0 MPa to determine the total gas uptake, induction time and rate of hydrate formation. The observed trends indicated that higher driving force resulted in higher gas consumption and significantly reduced induction time. For the same driving force, higher gas consumption and shorter induction time was achieved by THF as compared to TBAB. 5.53 mol% THF attained higher gas consumption than 1.0 mol% THF whereas 3.0 mol% TBAB attained lower gas consumption than 0.3 mol% TBAB. A highest gas uptake of 51.95 (+/- 5.183) mmol of gas/mol of water and a highest rate of 51.21(+/- 8.91) mol.min(-1).m(-3) were obtained for 5.53 mol% THF at 6.0 MPa and 279.2 K. Overall, this study indicated better hydrate formation kinetics with the use of THF in an FBR configuration for CO2 capture from a fuel gas mixture. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Fixed bed reactor; Gas hydrates; Pre-combustion capture; Promoters

Impact of experimental pressure and temperature on semiclathrate hydrate formation for pre-combustion capture of CO2 using tetra-n-butyl ammonium nitrate - Babu, Ponnivalavan; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
TBANO(3) (tetra-n-butyl ammonium nitrate) is a promising liquid phase promoter for capturing CO2 via HBGS (hydrate based gas separation) technology. In this study, the impact of experimental pressure and temperature on formation of mixed CO2-H-2-TBANO(3) semiclathrate hydrate for the optimum 1.0 mol% TBANO(3) reported by Babu et al. [1] was investigated. Experimental pressures of 3.0, 4.5 and 6.0 MPa and temperatures of 274.2, 276.2 and 278.2 K were employed. Irrespective of the experimental pressure, shorter induction time was observed for experiments conducted at 274.2 K when compared to the experiments at other temperatures. At a given pressure, the total gas uptake increased with increase in experimental temperature. Similarly at a given temperature, the total gas uptake increases with an increase in pressure. Higher rate of hydrate formation was observed at experimental pressure of 6.0 MPa than at 3.0 and 4.5 MPa irrespective of the experimental temperature. The CO2 composition in hydrate was between 87.5 and 93.2 mol%. Finally, the gas consumption for 1.0 mol% TBANO(3) as promoter was much higher than other promoters of quaternary salts like tetra-n-butyl ammonium bromide and tetra-n-butyl ammonium fluoride at comparable concentration and driving force. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Semi-clathrates

Impact of pressure and temperature on tetra-n-butyl ammonium bromide semi-clathrate process for carbon dioxide capture - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (International Conference on Applied Energy, ICAE2014, 2014)
The pre-combustion capture of CO2 in an IGCC power plant employing the hydrate based gas separation (HBGS) process is a novel method currently receiving attention around the world. Tetra-n-butyl ammonium bromide (TBAB) is a promoter that has been shown to improve the efficiency of hydrate formation. In this study, the effect of temperature and pressure on 0.3 mol% TBAB solution is investigated. The induction time for the experiments conducted at 6.0 MPa and 274.8 K was found to be lower, while nucleation became increasingly random as temperature is increased and pressure is reduced. Total gas uptake and normalized rate of hydrate formation (NR5) is also the highest for the experiments conducted at 6.0 MPa and 274.8 K. However, it was found that the hydrate phase CO2 composition remains relatively constant at both reduced temperatures and pressures. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; Promoters; tetra-n-butyl ammonium bromide

Unusual behavior of propane as a co-guest during hydrate formation in silica sand: potential application to seawater desalination and carbon dioxide capture - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Chemical Engineering Science, 2014)
We report an unusual behavior of hydrate formation in silica sand with gas mixtures containing propane as a co-guest. Based on morphology study we observed that propane as a co-guest has the ability to draw water dispersed in silica sand to the hydrate formation region and showed a tendency to result in drastic hydrate growth due to the migration of water molecules to the gas phase region. Hydrate nucleation occurred in the interstitial pore space between the silica sand particles and hydrate growth occurred in the gas phase above the silica sand bed and to sustain the hydrate growth, dispersed water was drawn towards the hydrate growth front. In addition, we elucidated the effect of sand bed height to maximize the growth rates utilizing this behavior that results in enhanced kinetics. We propose conceptual designs for utilizing this behavior of propane as a co-guest in sand for seawater desalination and an innovative approach to simultaneously capture carbon dioxide and desalinate seawater. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Desalination; Enhanced kinetics; Gas hydrates; Propane hydrate: pre-combusuon capture

Review of the hydrate based gas separation (HBGS) process for carbon dioxide pre-combustion capture - Babu, Ponnivalavan; Linga, Praveen; Kumar, Rajnish; Englezos, Peter (Energy, 2015)
In this work, a systematic review of the literature work done so far on the use of hydrate crystallization as a basis to develop data for the hydrate based gas separation (HBGS) process for the capture of CO2 from fuel gas mixtures is presented. Such a gas mixture may arise in integrated gasification combined cycle (IGCC) power plants. A thorough assessment of the thermodynamic, kinetic factors and economic aspects of the HBGS process and critical comments are presented. Compared with competing technologies, high CO2 capacity and the use of water as a solvent are key advantages for the HBGS process for CO2 capture. Furthermore, in this review, a snapshot of the current state-of-the-art is presented and further research and development opportunities and pathways for commercializing the HBGS process for pre-combustion capture of CO2 from IGCC power plants are discussed. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; IGCC plants; Pre-combustion capture

Hydrate-based carbon capture process: assessment of various packed bed systems for boosted kinetics of hydrate formation - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Balomajumder, Chandrajit; Kumar, Pushpendra (Journal of Energy Resources Technology-Transactions of the ASME, 2021)
The case for developing novel technologies for carbon dioxide (CO2) capture is fast gaining traction owing to increasing levels of anthropogenic CO2 being emitted into the atmosphere. Here, we have studied the hydrate-based carbon dioxide capture and separation process from a fundamental viewpoint by exploring the use of various packed bed media to enhance the kinetics of hydrate formation using pure CO2 as the hydrate former. We established the fixed bed reactor (FBR) configuration as a superior option over the commonly used stirred tank reactor (STR) setups typically used for hydrate formation studies by showing enhanced hydrate formation kinetics using the former. For the various packing material studied, we have observed silica gel with 100 nm pore size to return the best kinetic performance, corresponding to a water to hydrate conversion of 28 mol% for 3 h of hydrate growth. The fundamental results obtained in the present study set up a solid foundation for follow-up works with a more applied perspective and should be of interest to researchers working in the carbon dioxide capture and storage and gas hydrate fields alike.
Keywords: air emissions from fossil fuel combustion; Carbon dioxide capture; combustion of waste; Fixed bed reactor; fuel combustion; Gas hydrate; hydrates; kinetics; Silica gel